Gating control effect facilitates excellent gas selectivity in a novel Na-SSZ-27 zeolite. Issue 34 (30th March 2021) - Zhao, Chao; Yuan, Jiamin; Tang, Xiaomin; Chen, Wei; Yi, Xianfeng; Xia, Hongqiang; Liu, Wentao; Zheng, Anmin; Liu, Zhiqiang
Abstract : A novel Na-SSZ-27 zeolite was demonstrated to possess excellent H2 /CO2 diffusion selectivity due to the crucial effect of the "gating control" of the 8-ring windows. Abstract : A novel Na-SSZ-27 zeolite was demonstrated to possess excellent H2 /CO2 diffusion selectivity of more than 100. This investigation highlights the crucial effect of the "gating control" of the 8-ring windows on the separation, where sodium cations act as gates to selectively control the diffusion of CO2 and promote the selectivity for H2 .